Pengenalan dan Pencegahan Obesitas Pada Kalangan Remaja - Keni Ida Cahyani; Pandu Nurdiansyah; Witri Fajarwati; Yunita Safitri; Yolanda Febriana; Yadi Aditya Prawira; Widia Ningsih; Nurfaiza Safitri; M. Hilmy Alfaridzi; Ani Mulyani; Fatwa Rachmawan (Universitas Malahayati Lampung, 2026)
ABSTRAK Pada kegiatan promosi kesehatan dengan tema